A monolithic algorithm for the flow simulation of flexible flapping wings. (April 2019) - Yang, Tao; Wei, Mingjun; Jia, Kun; Chen, James
It has been a challenge to simulate flexible flapping wings or other three-dimensional problems involving strong fluid–structure interactions. Solving a unified fluid–solid system in a monolithic manner improves both numerical stability and efficiency. The current algorithm considered a three-dimensional extension of an earlier work which formulated two-dimensional fluid–structure interaction monolithically under a unified framework for both fluids and solids. As the approach is extended from a two-dimensional to a three-dimensional configuration, a cell division technique and the associated projection process become necessary and are illustrated here. Two benchmark cases, a floppy viscoelastic particle in shear flow and a flow passing a rigid sphere, are simulated for validation. Finally, the three-dimensional monolithic algorithm is applied to study a micro-air vehicle with flexible flapping wings in a forward flight at different angles of attack. The simulation shows the impact from the angle of attack on wing deformation, wake vortex structures, and the overall aerodynamic performance.